Application and prospects of multi-phase pipeline simulation technology in empowering the intelligent oil and gas fields - Gong, Jing; Kang, Qi; Wu, Haihao; Li, Xiaoping; Shi, Bohui; Song, Shangfei (Journal of Pipeline Science and Engineering, 2023)
This paper reviews the application of multiphase flow simulation technology for constructing intelligent oil and gas fields. By utilizing the theoretical multiphase flow simulation model and solution algorithm, the practical engineering application of this technology in various oil and gas gathering and transportation system scenarios, including subsea production systems in offshore oil and gas fields, well site gathering and transportation production systems in onshore gas fields, and platform gathering and transportation production systems, was assessed and described. In addition, the role of multiphase flow simulation technology in intelligent oilfield surface production was discussed from the perspective of surface oil and gas pipeline networks and intelligent oilfield operations. Moreover, the future development prospects of multiphase pipeline transport simulation technology were proposed, providing a reference for improving related research and constructing intelligent oilfields.